Chasing the Falconers - Korman, Gordon (New York : Scholastic, 2005)
Aidan and Meg Falconers' parents are facing life in prison unless Aidan and Meg can prove their innocence, but first they must excape from a juvenile detention center and elude both the authorities and a sinister attacker who has his own reason to stop them.
"Chase #1."
"An Apple paperback."
680
Accelerated Reader AR
Keywords: Brothers and sisters -- Juvenile fiction; Fugitives from justice -- Juvenile fiction; Adventure fiction